LITERATURE REVIEW: THE BENEFITS OF DANCE THERAPY FOR ELDERY [KAJIAN LITERATUR: MANFAAT TERAPI MENARI UNTUK LANSIA] - Ni Luh Putu Dian Yunita Sari; Etty Rekawati (Universitas Pelita Harapan, 2019)
A setback that occurs in elderly impacted on the decline in the physical aspect, psychological, social and environmental. This calls for a unexplainable intervention that can reach all of that experienced the decline. Dancing is one of physical activity therapy that often used in the world for the elder, both facing health problems or a healthy elderly. A literature review uses PRISMA statement as a guide search of articles of the three databases such as Science Direct, Scopus and ProQuest. The results of the analysis ten elected articles are dance therapy very effective and has benefit to the physical aspect, psychological, social and environmental. The benefits have positive implications for the potential ability of the elderly to live their lives so that the quality of life of the elderly increases. The application of dance therapy has potential to be done in the order of primary health services in Indonesia which is supported by many variance of Indonesian dances so that the related research and publications are needed to influence the health care policy of the elderly.BAHASA INDONESIA ABSTRAK Kemunduran yang terjadi pada lansia berdampak pada penurunan aspek fisik, psikologis, sosial dan lingkungan. Hal ini membutuhkan suatu intervensi yang dapat menjangkau seluruh aspek yang mengalami penurunan tersebut. Terapi menari adalah salah satu terapi aktifitas fisik yang banyak dimanfaatkan di dunia untuk lansia, baik yang mengalami masalah kesehatan ataupun lansia yang sehat. Kajian pustaka ini menggunakan PRISMA statement sebagai panduan pencarian artikel penelitian dari tiga database yaitu Science Direct, Scopus dan ProQuest. Hasil analisis sepuluh artikel penelitian terpilih menunjukkan bahwa terapi menari efektif dan memiliki manfaat untuk aspek fisik, psikologis, sosial dan lingkungan lansia. Manfaat yang dihasilkan berimplikasi positif pada kemampuan potensial lansia dalam menjalani hidupnya sehingga kualitas hidup lansia meningkat. Penerapan terapi menari ini potensial dilakukan di tatanan pelayanan kesehatan primer di Indonesia yang didukung banyaknya pilihan tarian Indonesia sehingga penelitian dan publikasi terkait diperlukan untuk memengaruhi kebijakan pelayanan kesehatan lansia.